Amino acid metabolism in glioblastoma pathogenesis, immune evasion, and treatment resistance - Shriyansh Srivastava; Robab Anbiaee; Mohammad Houshyari; Laxmi; Sathvik Belagodu Sridhar; Sumel Ashique; Sadique Hussain; Sachin Kumar; Tahreen Taj; Zeinab Akbarnejad; Farzad Taghizadeh-Hesary (Cancer Cell International)
Abstract Glioblastoma (GBM) ranks among the most lethal primary tumors of the central nervous system. This is partly due to its complex intracellular metabolism and interactions with the surrounding tumor microenvironment (TME). Compelling evidence represents that altered amino acids (AAs) metabolism plays a crucial role in both areas. The role of AAs and their metabolites in glioma biology is an emerging topic. Therefore, this review was conducted to summarize the current knowledge about the molecular mechanisms by which AAs participate in the GBM pathogenesis. AAs can directly influence tumor progression by affecting tumor cell metabolism or indirectly by releasing bioactive agents through particular metabolic pathways. This review begins by examining the metabolic pathways of essential AAs, such as tryptophan, tyrosine, and phenylalanine, which contribute to synthesizing critical neurotransmitters and shape tumor metabolism signatures. We explore how these pathways impact tumor growth and immune modulation, focusing on how AAs and their metabolites can promote malignant properties in GBM cells. AAs also play a pivotal role in reprogramming the TME, contributing to immune evasion and resistance to therapy. The review further discusses how tumor metabolism signatures, influenced by AA metabolism, can enhance the immunosuppressive microenvironment, providing new avenues for targeted immunotherapies. Finally, we outline potential therapeutic strategies to modulate AA metabolism and emphasize critical opportunities for future research to improve GBM management.